Development of nanoemulgel of 5-Fluorouracil for skin melanoma using glycyrrhizin as a penetration enhancer - Nimish Gupta; G.D. Gupta; Karan Razdan; Norah A. Albekairi; Abdulrahman Alshammari; Dilpreet Singh (Elsevier, 2024)
The purpose of this study was to enhance the topical delivery of 5-Fluorouracil (5-FU), a cancer treatment, by developing a nanoemulgel formulation. Glycyrrhizin (GLY), a natural penetration enhancer has been investigated to exhibit synergistic effects with 5-FU in inhibiting melanoma cell proliferation and inducing apoptosis, Hence, GLY, along with suitable lipids was utilized to create an optimized nanoemulsion (NE) based gel. Solubility studies and ternary phase diagram revealed isopropyl myristate (IPM), Span 80, Tween 80 as Smix and Transcutol P as co-surfactant. IPM demonstrates excellent solubilizing properties facilitates higher drug loading, ensuring efficient delivery to the target site.,The optimized formulation consisting of 40 % IPM, 30 % of mixture of Tween80: Span80 (Smix) and 15 % Transcutol P provides with a nanometric size of 64.1 ± 5.13 nm and drug loading of 97.3 ± 5.83 %. The optimized formulation observed with no creaming and breakeing of NE and found thermodynamically stable during different stress conditions (temperatures of 4.0 °C and 45.0 °C) and physical thawing (−21.0 ± 0.50 °C to 20.0 ± 0.50 °C). The NE was then transformed into a nanoemulgel (NEG) using 1.5 % w/w Carbopol base and 0.1 % w/w glycyrrhizin. The ex vivo permeability studies showed significant enhancements in drug permeability with the GLY-based 5-FU-NEG formulation compared to pure 5-FU gel in excised pig skin upto1440 min in PBS 7.4 as receptor media. The IC50 values for Plain 5-FU gel, 5-FU-NEG, and GLY-based 5-FU-NEG were found to be 20 µg/mL, 1.1 µg/mL, and 0.1 µg/mL, respectively in B16F10 cell lines. The percentage intracellular uptake of GLY-5-FU-NEG and 5-FU-NEG was found to be 44.3 % and 53.6 %, respectively. GLY-based 5-FU-NEG formulation showed alterations in cell cycle distribution, in compared to 5-FU-NE gel. The overall findings suggest that the GLY-based 5-FU-NEG holds promise for improving anti-melanoma activity.